2018
DOI: 10.1007/s10701-017-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Problem of Proper Time in Weyl Space–Time

Abstract: We discuss the question of whether or not a general Weyl structure is a suitable mathematical model of space-time. This is an issue that has been in debate since Weyl formulated his unified field theory for the first time. We do not present the discussion from the point of view of a particular unification theory, but instead from a more general standpoint, in which the viability of such a structure as a model of space-time is investigated. Our starting point is the well known axiomatic approach to space-time g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 25 publications
(38 reference statements)
3
45
0
Order By: Relevance
“…In addition to that, in the limit in which the length curvature F µν goes to zero Perlick's time reduces to the Riemannian or WIST proper time. Recently, it was shown the equivalence between this definition and the one given in the well-known paper by Ehlers, Pirani, and Schild (EPS) [8,9]. The latter was entirely based on axiomatic approach which leads to a Weyl structure as the most suitable model for spacetime.…”
Section: Weyl Geometrymentioning
confidence: 92%
See 4 more Smart Citations
“…In addition to that, in the limit in which the length curvature F µν goes to zero Perlick's time reduces to the Riemannian or WIST proper time. Recently, it was shown the equivalence between this definition and the one given in the well-known paper by Ehlers, Pirani, and Schild (EPS) [8,9]. The latter was entirely based on axiomatic approach which leads to a Weyl structure as the most suitable model for spacetime.…”
Section: Weyl Geometrymentioning
confidence: 92%
“…where the overdot means derivative with respect to the curve's parameter [8] . It has also been shown that Perlick's time has all the properties a good definition of proper time in a Weyl space-time should have, such as, Weyl-invariance, positive definiteness, additivity.…”
Section: Weyl Geometrymentioning
confidence: 99%
See 3 more Smart Citations